EFISIENSI TEKNIK PERBANKAN INDONESIA PASCAKRISIS EKONOMI: SEBUAH STUDI EMPIRIS PENERAPAN MODEL DEA - Sutawijaya, Adrian; Lestari, Etty Puji (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2009)
This study analyzes the performance of the Indonesian banking sector efficiency and peeling technique factors that lead to inefficiencies that could reduce the banks internal performance using Data Envelopment Analisys model (DEA). Research on the efficiency of banking techniques in Indonesia in 2000-2004 conducted using secondary data analysis including balance sheets and income statements of banks in Indonesia 12, the number of bank offices, and the number of bank employees in 2000 until 2004. Results of DEA analysis for the entire group decreased efficiency of banks during the crisis, except Bank Mandiri. This means that Bank Mandiri has the best performance compared to other banks. Inefficiency generally caused by using less than optimal inputs to produce output. Inputs that have not been completely allocated are assets and labor are not on optimizing the range below 50 percent. To produce the maximum efficiency, the bank must increase the use of its inputs to 100 percent.